2009
DOI: 10.1186/1472-6769-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic inhibition of topoisomerase II by a novel rationally designed ATP-competitive purine analogue

Abstract: Background: Topoisomerase II poisons are in clinical use as anti-cancer therapy for decades and work by stabilizing the enzyme-induced DNA breaks. In contrast, catalytic inhibitors block the enzyme before DNA scission. Although several catalytic inhibitors of topoisomerase II have been described, preclinical concepts for exploiting their anti-proliferative activity based on molecular characteristics of the tumor cell have only recently started to emerge. Topoisomerase II is an ATPase and uses the energy derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 45 publications
3
66
0
Order By: Relevance
“…2A). Consistent with previous reports (Morris et al, 2000;Chène et al, 2009), the closed clamp inhibitor ICRF-193 also reduced topo IIa-mediated ATP hydrolysis ( Fig. 2A).…”
Section: Resultssupporting
confidence: 92%
“…2A). Consistent with previous reports (Morris et al, 2000;Chène et al, 2009), the closed clamp inhibitor ICRF-193 also reduced topo IIa-mediated ATP hydrolysis ( Fig. 2A).…”
Section: Resultssupporting
confidence: 92%
“…Recent studies reported the synthesis of new derivatives such as the purine analog quinoline aminopurine compound 1 (Chène et al, 2009), thiosemicarbazones (Huang et al, 2010), N-fused imidazoles (Baviskar et al, 2011), or xanthone analogs (Jun et al, 2011), which inhibit the catalytic activity of Top2␣ by an ATPcompetitive mechanism. Apart from quinoline aminopurine compound 1, which inhibits both isoforms (Chène et al, 2009), it is not known whether these derivatives also inhibit the catalytic activity of Top2␤, which is expressed in postmitotic cells (Watanabe et al, 1994;Lyu and Wang, 2003) and nonproliferating tissues such as the adult heart (Capranico et al, 1992). Development of a selective Top2␣ catalytic inhibitor would therefore be useful because Top2␤ was shown to be involved in anthracyclin-induced cardiotoxicity and was also required for neuronal differentiation and the expression of a number of neuronal genes (Lyu and Wang, 2003;Nur-EKamal et al, 2007).…”
Section: Top2α Top2βmentioning
confidence: 99%
“…Activity against topoisomerase II was done as previously described (24). The activity of NVP-BEP800 was evaluated against a panel of kinases consisting of HER-1, KDR, Flt-3, IGF-1R, Tek, c-src, c-Met, Ret, JAK-2, EphB4, FGFR-3-K650E, Axl, FAK, c-Abl, c-Abl-T315I, PKA, CDK1/B, PKB/Akt, PDK1, and B-Raf-V599E.…”
Section: Hsp90 Binding and Selectivity Assaysmentioning
confidence: 99%